Liberalisation, Concentration and Diversification: Business Groups in India, 2000-2020 - Simon Commander; Saul Estrin; Naveen Thomas; Varun Lingineni (Institute of Labor Economics (IZA), 2024)
We analyse changes in market structure in India between 2000 and 2020 using a rich dataset at high levels of disaggregation. We examine the extent to which business groups – notably family-owned groups – have maintained dominant market positions in the Indian economy. We focus on two key dimensions. The first is the extent of concentration in markets and market shares by industry. The second concerns the dynamics and the extent to which business groups have focussed on consolidating their position in specific, narrow sectors or, rather, entered new sectors and diversified. We find that while market concentration has been falling, a bloc of high concentration sectors remains. Further, diversification has been actively pursued across sectors by most business groups. While this points to greater competition among business groups, the ratio of revenues to variable costs – a measure of the markup – has shifted upwards, particularly after 2013. The weight and persistence of these large business groups in the economy, as measured by the ratio of their revenues to GDP, has also increased. Finally, we discuss possible policy options.
Keywords: D22; L1; L11; O14; O25; 330; market concentration; India; business groups; Hirschman Herfindahl Indices; diversification